(Table 1) Borings chips and/or borings of the ichnogenus Entobia at DSDP Hole 74-526A - Dieter K Fütterer (PANGAEA, 1984)
Pelagic carbonate oozes of DSDP Site 526 contain remnants of the activity of boring sponges of the family Clionidae: (1) the borings themselves = ichnogenus Entobia and (2) the characteristically shaped boring chips as a finegrained sediment component.
Supplement to: Fütterer, DK (1984): Evidence of Clionid sponges in sediments of the Walvis Ridge, southeastern Atlantic Site 526, Deep Sea Drilling Project Leg 74. In: Moore, TC Jr; Rabinowitz, PD; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 74, 557-560, https://doi.org/10.2973/dsdp.proc.74.113.1984